UNIFEM: Defensa y promoción de la mujer y su derecho a la educación / UNIFEM: Defence and promotion of women and their right to education - Canorea Martínez, Nuria (Journal of Supranational Policies of Education (JOSPOE), 2016)
ABSTRACT The United Nations Development Fund for Women (UNIFEM) has done a lot of work since its founding (1984) until its merger in UN WOMEN (2010), in different areas: reducing feminized poverty, ending violence against women, reverse the spread of HIV /AIDS among women and girls, and achieving gender equality in the political, economic, social and cultural spheres. It has supported efforts by governments and civil institutions that are focusing to improve the quality of life of women and protection of their rights. One of the efforts is education. Given the disparity in access fees and training of women and girls, it becomes a key tool to achieve not only parity and gender equality, but the promotion and empowerment of women, favoring their autonomy and development, to participate in key decision-making bodies. Key words: UNIFEM, women, parity, rights, education. RESUMEN El Fondo de Desarrollo de las Naciones Unidas para la Mujer (UNIFEM) ha realizado una ingente labor desde su fundación (1984) hasta su fusión en UN WOMEN (2010), en diferentes ámbitos: reducir la feminización de la pobreza, poner fin a la violencia contra las mujeres, contrarrestar la propagación del VIH/SIDA entre las mujeres y niñas, y lograr la igualdad de género en las esferas políticas, económicas, sociales y culturales. Para ello ha apoyado las iniciativas de gobiernos e instituciones civiles conducentes a mejorar la calidad de vida de las mujeres y la protección de sus derechos. Uno de ellos es la educación. Ante la disparidad de tasas en cuanto al acceso y formación de mujeres y niñas, aquélla se convierte en una herramienta clave para lograr no sólo la paridad e igualdad de sexos, sino la promoción y el empoderamiento de la mujer, para, favoreciendo su autonomía y desarrollo, participar en los principales órganos de toma de decisiones. Palabras clave: UNIFEM, mujer, paridad, derecho, educación.